2017
DOI: 10.1158/1538-7445.sabcs16-pd2-08
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD2-08: Neratinib + fulvestrant in ERBB2-mutant, HER2–non-amplified, estrogen receptor (ER)-positive, metastatic breast cancer (MBC): Preliminary analysis from the phase II SUMMIT trial

Abstract: Background: Somatic mutations in ERBB2 are a new class of oncogenic drivers in HER2–non amplified MBC. Neratinib is an irreversible pan-HER tyrosine kinase inhibitor that inhibits the growth of ERBB2-mutant breast tumors in preclinical models and has encouraging single-agent clinical activity in patients (pts) with ERBB2-mutant, HER2–non amplified MBC. Bi-directional signaling between HER2 and ER may limit the effectiveness of endocrine and HER2 directed therapy, if each is given alone, in ER+ MBC with ERBB2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Yet the majority of the patients with those HER2 mutations did not benefit from Nrb treatment alone. A recent preclinical study in ER+ MCF7 cells expressing HER2 kinase domain mutations (52), as well as early results from an additional clinical trial investigating the efficacy of Nrb + fulvestrant in ER+ metastatic breast cancer patients with HER2 mutations (SUMMIT, NCT01953926) (53), further support the notion that a simultaneous inhibition of ER (fulvestrant) and the mutant HER2 by irreversible TKIs is needed. However, a significant portion of patients did not benefit even with the combination of Nrb+fulvestrant while other patients developed acquired resistance.…”
Section: Discussionmentioning
confidence: 85%
“…Yet the majority of the patients with those HER2 mutations did not benefit from Nrb treatment alone. A recent preclinical study in ER+ MCF7 cells expressing HER2 kinase domain mutations (52), as well as early results from an additional clinical trial investigating the efficacy of Nrb + fulvestrant in ER+ metastatic breast cancer patients with HER2 mutations (SUMMIT, NCT01953926) (53), further support the notion that a simultaneous inhibition of ER (fulvestrant) and the mutant HER2 by irreversible TKIs is needed. However, a significant portion of patients did not benefit even with the combination of Nrb+fulvestrant while other patients developed acquired resistance.…”
Section: Discussionmentioning
confidence: 85%
“…We speculate these co-mutations resulted in increased dependence on the ERBB pathway and contributed to the tumor’s initial sensitivity to neratinib. Consistent with this speculation, preliminary results from the SUMMIT trial show that among 17 patients who exhibited clinical benefit from neratinib, 2 patients harbored ERBB3 missense mutations, whereas none of the 25 patients who did not benefit harbored ERBB3 alterations in their cancer (27). …”
Section: Discussionmentioning
confidence: 78%
“…Studies have shown that tumours carrying these activating HER2 mutations respond to treatment with the irreversible pan-HER kinase inhibitor neratinib [219,220]. Preliminary results from the ongoing SUMMIT trial, exploring the efficacy of neratinib in patients carrying activating HER2 and HER3 mutations, have been encouraging [221,222], while other work continues to investigate how specific mutations may impact responsiveness to this and other inhibitors [223].…”
Section: Somatic Mutations In Her2 As Biomarkersmentioning
confidence: 99%